2007
DOI: 10.1128/jvi.02303-06
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus NS1 Protein Degrades STAT2 by Using the Elongin-Cullin E3 Ligase

Abstract: Respiratory syncytial virus (RSV) infection causes bronchiolitis and pneumonia in infants.RSV has a linear single-stranded RNA genome encoding 11 proteins, 2 of which are nonstructural (NS1 and NS2). RSV specifically downregulates STAT2 protein expression, thus enabling the virus to evade the host type I interferon response. Degradation of STAT2 requires proteasomal activity and is dependent on the expression of RSV NS1 and NS2 (NS1/2). Here we investigate whether RSV NS proteins can assemble ubiquitin ligase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
226
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(236 citation statements)
references
References 37 publications
8
226
2
Order By: Relevance
“…In this line, we unveil for the first time that DUOX2 is critical for the outcome of respiratory virus infections through its key function in the establishment of the antiviral state specifically induced by the synergistic action of IFNβ and TNFα secreted during SeV infection. The capacity of RSV to counteract this novel antiviral pathway adds to its previously recognized capacity to interfere with other key antiviral events, including RIG-I-dependent signaling or IKKε, TRAF3 or STAT2 stability [33,34]. Altogether, these evasion mechanisms contribute to the development of RSV-associated diseases.…”
Section: Rsv Interferes With the Expression Of Duox2mentioning
confidence: 99%
“…In this line, we unveil for the first time that DUOX2 is critical for the outcome of respiratory virus infections through its key function in the establishment of the antiviral state specifically induced by the synergistic action of IFNβ and TNFα secreted during SeV infection. The capacity of RSV to counteract this novel antiviral pathway adds to its previously recognized capacity to interfere with other key antiviral events, including RIG-I-dependent signaling or IKKε, TRAF3 or STAT2 stability [33,34]. Altogether, these evasion mechanisms contribute to the development of RSV-associated diseases.…”
Section: Rsv Interferes With the Expression Of Duox2mentioning
confidence: 99%
“…RSV non-structural proteins have been shown to interact with several host nuclear, cytosolic and mitochondrial factors, leading to suppression of the antiviral response, cell cycle regulation, DNA damage repair and culminating in G 0 /G 1 phase cell cycle arrest (Atreya et al, 1998;Bossert et al, 2003;Boyapalle et al, 2012;Elliott et al, 2007;Lo et al, 2005;Munday et al, 2010;Munir et al, 2011;Ren et al, 2011;Schlender et al, 2000;Spann et al, 2004Spann et al, , 2005Wu et al, 2012;Xu et al, 2014). TGF-b expression during RSV infection has been shown to be important for cell cycle inhibition in the G 0 /G 1 phase (Gibbs et al, 2009;McCann & Imani, 2007;Wu et al, 2011) and miR-24 has been shown to be suppressed by TGF-b (Sun et al, 2008), as well as regulate TGF-b precursor processing (Luna et al, 2011).…”
Section: Rsv Ns1 Modulates Tgf-b Expression Via Klf6mentioning
confidence: 99%
“…Codon deoptimized RSV is attenuated in vitro, but evokes a strong humoral response upon vaccination and challenge (Meng et al, 2014). These and other immune modulators inhibit the development of the antiviral state (Bossert et al, 2003;Elliott et al, 2007;Goswami et al, 2013;Lo et al, 2005;Moore et al, 2008;Oshansky et al, 2009a;Spann et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations